2009
DOI: 10.1182/blood.v114.22.3040.3040
|View full text |Cite
|
Sign up to set email alerts
|

Factor XII Stimulates ERK1/2 and Akt through uPAR, Integrins, and the EGFR to Initiate Angiogenesis.

Abstract: 3040 Poster Board II-1016 The physiologic function of factor XII (XII) is not known. New interest in XII has occurred because XII KO mice are protected from thrombosis. Exposed arterial collagen, aggregated protein, RNA, and platelet polysomes are recently recognized entities in developing thrombus that promote XII autoactivation to XIIa increasing thrombus formation, independent of a role in hemostasis. However, these observations do not indicate a constitutive, physiologic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 0 publications
7
73
0
Order By: Relevance
“…KLKB1 has a known proteolytic function, activating a number of proteins including bradykinin and blood clotting factor XII (58). Interestingly, a FXII SNP demonstrated near genome-wide significance with serum scuPAR levels in the current study and FXII has been shown to interact with uPAR to stimulate ERK1/2 and Akt signaling pathways (59). KLKB1 has also been implicated in the stimulation of neutrophil chemotaxis, aggregation, and oxygen consumption (60).…”
Section: Discussionmentioning
confidence: 61%
“…KLKB1 has a known proteolytic function, activating a number of proteins including bradykinin and blood clotting factor XII (58). Interestingly, a FXII SNP demonstrated near genome-wide significance with serum scuPAR levels in the current study and FXII has been shown to interact with uPAR to stimulate ERK1/2 and Akt signaling pathways (59). KLKB1 has also been implicated in the stimulation of neutrophil chemotaxis, aggregation, and oxygen consumption (60).…”
Section: Discussionmentioning
confidence: 61%
“…FXII binds to urokinase plasminogen activator receptor or cross-talks with EGFR on HUVEC membranes, leading to activation of MAPK and Akt with subsequent proliferation and differentiation. 21 siRNAmediated knockdown of FXII resulted in a profound inhibition of AEG-1-induced angiogenesis, indicating a central role of FXII in this process. The question is, does AEG-1 also regulate FXII under normal conditions?…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, both FXII and TFF3 interacts with EGFR on ECs to augment proliferation and differentiation, hence angiogenesis. 21,24 Thus, there might be a key role of endothelial EGFR in mediating AEG-1 function, a hypothesis that needs to be experimentally validated.…”
Section: Discussionmentioning
confidence: 99%
“…Factor XII stimulates cell proliferation and angiogenesis through uPAR and HK blocks both. [15]. Like single-chain urokinase, FXII binding to uPAR initiates signaling through b 1 integrin and the epidermal growth factor to phosphorylate ERK1/2 and AktS 473 [15].…”
Section: The Protein Componentsmentioning
confidence: 99%